Settleable Matter from the Parcona Pond as a Soil Amendment for Semi-Arid Soils of Ica-Peru - Argota-Pérez, George; Belli-Carhuayo, Félix Ricardo; De la Torre-Castro, Rene Anselmo; Carrasco-Gonzáles, José Antonio (REVISTA TERRA LATINOAMERICANA, 2025)
Wastewater treatment in oxidation ponds primarily focuses on water purification, often overlooking the potential reuse of the accumulated sediments. The objective of this study was to describe the settleable matter from the oxidation pond in Parcona and assess its potential value for semiarid soils in Ica, Peru. A descriptive study design was applied in the oxidation pond, where five sampling lines (SL-1, SL-2, SL-3, SL-4, and SL-5) were established to ensure representative spatial sampling. In each sampling line, three sediment samples were collected and subsequently homogenized to form a composite sample, which was analyzed in duplicate to determine pH, organic matter content, texture, nitrogen, and phosphorus levels. The main results indicated neutral pH values ranging from 6.6 to 7.3. Organic matter content varied from moderate to very high (2.21%-13.87%). Textural analysis showed high clay content in SL-1 (11.3 g cm-³) and SL-2 (12.3 g cm-³), while SL-3 (73.8 g cm-³) and SL-4 (65.8 g cm‑³) were predominantly silt. Nitrogen levels were elevated in SL-2 (1092 mg kg-1) and SL-3 (1321 mg kg-1), and phosphorus was consistently high across all sampling lines. The physicochemical variability of the sediment load reflects complex sedimentation processes that had not been previously characterized. The primary value of this finding lies in the potential use of this biosolid as an agricultural fertilizer; however, variability in pH, organic matter, and texture necessitates careful management to avoid adverse effects on agricultural soils. Overall, the sedimentable material from the oxidation pond exhibited exploitable nutrient properties, reinforcing its value as a fertilizer for semiarid soils within the framework of a circular economy.